Signaling soft power through medal success: China as an example - Liu, D. (Sport in Society: Cultures, Commerce, Media, Politics, 2020)
Using China as an example, this study seeks to examine whether and how a country`s elite sport success would affect its soft power from international audience`s perspective. Data were collected from residents of Paris through self-completion structured questionnaires. While the results of the study showed varied improvement on three national image dimensions, respondents` perception about China`s government and policy worsened. Drawing on costly signaling theory and attribution theory, Olympic involvement and goodwill were also proposed and confirmed as antecedent factors influencing soft power impact through elite sports. The results not only provided empirical evidence whether Olympic achievement would actually affected a country`s soft power, but offered insights on the mechanisms at work behind that effect. A number of practical implications were also drawn with a view to leveraging soft power impact of elite sport success.